Pelaksanaan Prinsip Syariah dalam Akad dan Penyelessaian Segketa pada Lembaga Perbankan Syariah di Indonesia - Didiek Noeryono Basar (Justicia Islamica, 2013)
Murabahah is often equated with ordinary credit agreements, only the name is changed to murabahah or sale and purchase. It should be noted that the draft sharia agreement is also a standard contract issued by sharia banking in carrying out its financial transactions, the same as the agreement implemented by conventional banking. From the existence of a contract in the form of a standard draftSometimes it also causes a dispute. In Law No. 3 of 2006 Jo Law No. 50 of 2009 concerning Religious Courts, for the settlement of sharia disputes related to the implementation of contracts implemented by Sharia Banking, it should be the authority of the Religious Court. However, the fact is that many Shari'ah banking cases relating to the execution of contracts are delegated and handled by the Religious Court.contracts are delegated and handled by the District Court. Therefore, there needs to be firmness in the application of a norm, so that it can be implemented properly.